Pengalaman Perawat Dalam Memberikan Layanan Melalui Sistem BPJS (Badan Penyelenggara Jaminan Sosial) - Lailatul Kodriyah; Ronal Surya Aditya; Listyawati Ratna Ningrum (Jurnal Keperawatan, 2020)
BPJS is one of the government policies in the health sector. This BPJS program established by the government is used as one of the solutions to solve problems related to health problems that arise. This study aims to find out more about the experience of nurses in providing services with the BPJS system. This research was conducted descriptively Qualitative research using a phenomenological approach was carried out on 20 to 27 November 2019. Data were obtained by in-depth interviews with nurses working in Malang Hospital and analyzed the data analysis process with Interpretative Phenomenological Analysis (IPA). The population of this study was 5 respondents. The method of selecting participants was carried out using a purposive sampling technique. Age of respondents 30 to 45 years. The results found 3 themes, namely: service incentives, satisfaction and service. Conclusion: One of the services involved in the BPJS program is Nurse. those in conducting services have the right to service incentives, because that has several obstacles that create dissatisfaction. Health workers already have maximum performance. This research is expected in the future can be the basis for making decisions for awarding and better service systems. Further research recommendations are about nurse satisfaction with services.